2007
DOI: 10.1073/pnas.0706578104
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pathways of genomic progression to benign and malignant tumors of the liver

Abstract: We used several of the genetic lesions commonly associated with human liver tumors to reconstruct genetic progression to hepatocellular carcinoma and adenoma in mouse models. We initiated tumorigenesis with a transgene of the protooncogene MET or by hydrodynamic transfection of MET in combination with other genes into the livers of adult animals. Hepatocellular carcinoma in both instances arose from cooperation between MET and constitutively active versions of ␤-catenin. In contrast, adenomas were produced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
187
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(197 citation statements)
references
References 30 publications
5
187
0
Order By: Relevance
“…A recent report showed that c-Met overexpression in transgenic mice can also induce Afp + HCCs that express Dlk1 and a subset (23 of 42) of the Rian-Mirg microRNAs (18). However, in this model additional secondary mutations are required for HCC formation (39), and c-Met was not overexpressed in the mouse tumors we produced by gene targeting (Table S3).…”
Section: Discussionmentioning
confidence: 92%
“…A recent report showed that c-Met overexpression in transgenic mice can also induce Afp + HCCs that express Dlk1 and a subset (23 of 42) of the Rian-Mirg microRNAs (18). However, in this model additional secondary mutations are required for HCC formation (39), and c-Met was not overexpressed in the mouse tumors we produced by gene targeting (Table S3).…”
Section: Discussionmentioning
confidence: 92%
“…Co‐activation of MET and β‐catenin often occurs in HCC 22. Codelivery of both MET and CAT (ΔN90‐β‐catenin, exon 3 deleted), but neither MET nor CAT alone, into mouse livers using the sleeping beauty transposon system efficiently induces HCC within several weeks 22, 23, 24. Therefore, this model (referred to here as MET/CAT) is useful for studying the functions of genes in hepatocarcinogenesis because of its clinical relevance and efficiency of HCC induction.…”
Section: Resultsmentioning
confidence: 99%
“…For the c‐met (MET)/constitutively active β‐catenin (CAT)‐driven HCC model,19, 22, 23, 24 55 μg of total plasmids, encoding the sleeping beauty transposase (HSB2) and transposons with oncogenes MET/CAT and gaussia luciferase (Gluc) (22.5 μg pT3‐EF1a‐c‐MET [human], 22.5 μg pT3‐EF1a‐DN90‐β‐catenin [human], 5 μg pT3‐Gluc1, and 5 μg HSB2) were injected hydrodynamically into age‐ and sex‐matched mice. Six weeks after MET/CAT injection, mice were treated with vehicle (30% captisol), ceritinib (25 mg/kg), sorafenib (25 mg/kg), or a combination of ceritinib and sorafenib by oral gavage daily for 4 weeks prior to being sacrificed.…”
Section: Methodsmentioning
confidence: 99%
“…Activation of c-Met signaling and β-catenin mutations are frequent genetic occurrences observed in liver cancer initiation (9)(10)(11). Previous studies have reported that c-Met and β-catenin are coactivated in HCC, and possess a possible correlation with hepatic carcinogenesis (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Following the review of previous studies on FAK, c-Met and β-catenin oncoproteins, their correlation with HCC has been identified in a variety of studies (12,13,(18)(19)(20)(21)(22). However, the intercorrelation among them requires further investigation.…”
Section: Introductionmentioning
confidence: 99%